1976
DOI: 10.1159/000180715
|View full text |Cite
|
Sign up to set email alerts
|

Intrafamily Identity and Home Dialysis Success

Abstract: The entire family participates in the success of the home dialysis patient. Isolation and study of discrete quantifiable aspects of behavior within the family may allow identification of patients with a greater risk of failure, thus making it possible to help such patients succeed. A single such factor, ‘intrafamily identity’, measured in each of 40 diverse families before one family member began a home dialysis program, was found to correlate with success in the program 1 year later. This finding also may con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1984
1984
1997
1997

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Family relationships was identified as an area important to quality of life by 227 adults with chronic illnesses (Burckhardt, Woods, Schultz, & Ziebarth, 1989). In studies of dialysis patients, investigators have reported that family life has profound influence on patient adjustment, which has been found to be significantly correlated with quality of life (Dimond, 1979;Murphy, 1982;Pentecost, Zwerens, & Manuel, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Family relationships was identified as an area important to quality of life by 227 adults with chronic illnesses (Burckhardt, Woods, Schultz, & Ziebarth, 1989). In studies of dialysis patients, investigators have reported that family life has profound influence on patient adjustment, which has been found to be significantly correlated with quality of life (Dimond, 1979;Murphy, 1982;Pentecost, Zwerens, & Manuel, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Compliant as compared to noncompliant HD patients have fewer family problems and receive more assistance from their spouses [7] and have better communication within the family [30], In addition, they report stronger family members' expectations of their compliance [14], less negative illness impact on family function [10], and have higher family functioning in executive and taskoriented roles [19], Positive stalT member evaluation of HD patients and realistic expectations of patient rehabil itation have also been associated with good compliance [3. 14.…”
Section: Determinants For Compliance In Esrd Patientsfactors Related mentioning
confidence: 99%
“…Yet, despite a growing recognition of the impact of chronic, disabling medical illness on family life (15, 19, 25, 26, 28), and despite a comparable appreciation of the role of the family in the success or failure of adaptation to disabling illnesses (3, 4, 12, 20, 21, 30), there have been remarkably few psychosocial interventions focused on family issues, needs, and stresses during the chronic phase of the illness. Those programs that do exist are designed primarily to provide ongoing education and supportive therapy to the individual patient alone.…”
mentioning
confidence: 99%